125Iodide as a surrogate tracer for epithelial chloride transport by the mouse large intestine in vitro. Issue 3 (25th January 2019) - Stephens, Christine E.; Whittamore, Jonathan M.; Hatch, Marguerite
Abstract : New Findings: What is the central question of this study? The tracer 36 Cl −, currently used to measure transepithelial Cl − fluxes, has become prohibitively expensive, threatening its future use. 125 Iodide, previously validated alongside 36 Cl − as a tracer of Cl − efflux by cells, has not been tested as a surrogate for 36 Cl − across epithelia. What is the main finding and its importance? We demonstrate that 125 I − can serve as an inexpensive replacement for measuring Cl − transport across mouse large intestine, tracking Cl − transport in response to cAMP stimulation (inducing Cl − secretion) in the presence and absence of the main gastrointestinal Cl − –HCO3 − exchanger, DRA. Abstract: Chloride transport is important for driving fluid secretion and absorption by the large intestine, with dysregulation resulting in diarrhoea‐associated pathologies. The radioisotope 36 Cl − has long been used as a tracer to measure epithelial Cl − transport but is prohibitively expensive. 125 Iodide has been used as an alternative to 36 Cl − in some transport assays but has never been validated as an alternative for tracing bidirectional transepithelial Cl − fluxes. The goal of this study was to validate 125 I − as an alternative to 36 Cl − for measurement of Cl − transport by the intestine. Simultaneous fluxes of 36 Cl − and 125 I − were measured across the mouse caecum and distal colon. Net Cl − secretion was induced by the stimulation of cAMP with a cocktail of forskolin (FSK) and 3‐isobutyl‐1‐methylxanthine (IBMX). Unidirectional fluxes of 125 I − correlated well with 36 Cl − fluxes after cAMP‐induced net Cl − secretion, occurring predominantly through a reduction in the absorptive mucosal‐to‐serosal Cl − flux rather than by stimulation of the secretory serosal‐to‐mucosal Cl − flux. Correlations between 125 I − fluxes and 36 Cl − fluxes were maintained in epithelia from mice lacking DRA (Slc26a3), the main Cl − –HCO3 − exchanger responsible for Cl − absorption by the large intestine. Lower rates of Cl − and I − absorption in the DRA knockout intestine suggest that DRA might have a previously unrecognized role in iodide uptake. This study validates that 125 I − traces transepithelial Cl − fluxes across the mouse large intestine, provides insights into the mechanism of net Cl − secretion and suggests that DRA might be involved in intestinal iodide absorption. Abstract :